Investigation of the influence of fulleren-containing oils on tribotechnical characteristics - Derkach, O.; Kobets, A.; Aulin, V.; Kabat, O.; Makarenko, D.; Hrynkiv, A.; Shchus, B.; Деркач, О. Д.; Кобец, А. С.; Аулін, В. В.; Кабат, О. С.; Макаренко, Д. А.; et al. (Rousse University, 2020)
The influence of fullerenes’ soot concentration, which added to oil М10г2к on few tribotechnical characteristics «steel-steel» was investigated. It was found, that optimal volume of fullerene soot in the oil was 0,1% of the weight. At this level of concentration can be seen the lowest values of coefficient of friction – 0,045, and intense of linear wearing - 2,7×10-9. Through optical investigation the participation of fullerene soot in surface forming mechanism and saturated with carbon was confirmed, it provided an increase in tribotechnical characteristics of the samples. Досліджено вплив концентрації сажі фулеренів, що додано в оливу М10г2к, на деякі триботехнічні характеристики «сталь-сталь». Було встановлено, що оптимальний вміст фуллеренової сажі в оливі становив 0,1% ваги. На цьому рівні концентрації видно найнижчі значення коефіцієнта тертя - 0,045, а інтенсивності лінійного зношування - 2,7 × 10-9. Завдяки оптичному дослідженню було підтверджено участь фуллеренової сажі в механізмі поверхневого формування та насиченого вуглецем, що забезпечило підвищення триботехнічних характеристик зразків.
Дослідження впливу фулеренвмісних олив на триботехнічні характеристики
Keywords: fullerene soot; oil; concentration; tribotechnical characteristics; фулеренова сажа; олива; концентрація; триботехнічні характеристики